THE LEADER'S PROFESSIONALISM IS IMPORTANT QUALITIES TO DETERMINE APPROACHES - kizi, Rozikova Nazokat Alisher (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
When it comes to the difference between the functions a leader should perform and the functions actually performed, there is no complete correspondence between them. The functions performed in practice are manifested through the current situation of the leader, the personality of a certain leader, the state of affairs in the organization and the characteristics of relations in society